A Cardiac Rehabilitation Program Supported by mHealth Technology: The MOVIDA.eros Platform - Silva, Emanuel (2018)
The cardiac rehabilitation backdrop in Portugal is lacking much-needed improvements in order to better serve patients with different heart conditions. Although the beneficial results of cardiac rehabilitation are widely acknowledged, it is not being implemented in an optimal way, with few rehabilitation centers irregularly distributed throughout the country. In this context, the opportunity arose to develop a project that would help to fill in this gap. MOVIDA.eros is an ongoing project aims to bring more people into cardiac rehabilitation programs and help physicians monitor their health anywhere they are. By using a mobile app and a web platform, the MOVIDA.eros project allows healthcare providers to be constantly connected to their patients and see whether they are following their recommendations and adhering to the program. In this paper, an overview will be provided on the current situation of cardiac rehabilitation programs in Portugal, including the main weaknesses and issues that should be addressed. The main features of both the mobile app and the web platform will also be discussed, as well as any challenges that might have come up during the development process.